Large herbivore stocking rate effects on plant palatability, forage preference and soil properties in an Alluvium Fynbos-Renosterveld mosaic - Mubamu Makady, Elvis (Stellenbosch : Stellenbosch University, 2009)
Thesis (MSc (Conservation Ecology and Entomology))--Stellenbosch University, 2009.